Effectiveness of Popliteal Nerve Block in below Knee Surgeries - Salman Mohsin, Nasir Ali Rahim Najjad, Zara Rizwan, Tooba Mughal, Shakil Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To observe the effectiveness of sciatic nerve block in popliteal fossa (popliteal nerve block) and saphenous nerve block on the medial site of upper tibia in local population Study design: Descriptive cross-sectional study Place and duration of study: Department of Anesthesia, The Indus Hospital, Karachi from 11th March 2013 to 15th March 2014. Methodology: One hundred and fourteen patients with elective operations like wound debridement of foot, amputation of toes were included. After 15 minutes of giving the block, and at the time of incision, the patient was asked about his/her pain level by showing the pain scale. If the patient points at level 0, the surgery was proceed and the block was termed as effective. Results: Most of the patients were between 51-70 years of age and mean age was 58.83±9.21 years. There were 73(64.04%) males and 41(35.96%) females. Seventy four (64.91%) were in ASA-III, 32(28.07%) were in ASAIV and 8(7.02%) were in ASAV. The pain was not reported in 103(90.35%) patients while 11(9.6%) had pain in which 4 patients had mild pain, 5 moderate and 2 had severe pain. Block was effective in 103(90.35%) cases and ineffective in 11(9.65%) cases. Conclusion: Sciatic nerve block in popliteal fossa (popliteal nerve block) and saphenous nerve block on the medial site of upper tibia be taken as an anaesthesia method for surgeries below the knee as well as for the control of the post-operative pain specifically in patients where spinal anaesthesia is not favorable Keywords: Below knee surgery, Sciatic nerve block, Popliteal nerve block